Moving objects database for GIS-based emergency response system - Habibi, Ridlwan (2010)
Road traffic accidents (RTA) are among the ten causes of death in the world (WHO, 2006).Just like any other emergency events, immediate response in RTA is extremely needed to minimize greater damage and casualties. In other words, an effective and efficient emergency response management is able to minimize unnecessary risks. Emergency Response System (ERS) is a very important application in today society. It is a system that designed to provide assistance to emergency responder to deal with emergency situation. The implementation of Geographic Information System (GIS) in ERS has become widely used nowadays. When responding to an incident, first responders can use GIS to identify the various resources required - police, ambulances, fire fighters in order to help respond to an emergency in a timely and efficient manner. Parallel to that, the overall objective in GIS for emergency response is to deliver accurate, appropriate timely information to all the parties involved in an emergency case at the proper stages of the emergency. From the previous statement, it is clearly stated that time is an inherent aspect in ERS. Moreover, it is apparent that ERS is an application that deals with not only with spatial but also with temporal aspects. Therefore, time must be treated as an integrated dimension rather than an attribute. However, in reality, most implementations of temporality in GIS database still treat the two as quite separate. For that reason, ERS requires the management of spatial and temporal data. As stated above, ERS deals not only with static but also dynamic object. Consequently, the implementation of Moving Objects Database (MOD)as a backend for ERS is necessary. The purpose of this study is to develop a generic model of MOD for ERS especially in RTA. A generic model of Moving Objects Database for GIS-Based Emergency Response System called MODGERS has been developed. The basic requirements to develop such system are discussed in this research. The integration of temporal element into the coordinate system as 3D (2D + time) is also highlighted. Furthermore, technique in querying current, future, continuous and past location of moving objects data is also presented. In this research, we use vector-based tracking to estimate the current location of the moving object. On the other hand, the segment-based tracking is used to solve future and past query problems. A real time simulation has been conducted to validate the model and query operations. Vector-based tracking with additional factor of connected segment and segment direction is introduced to solve the current query. In future query, the used of segment-based tracking is explained while database view is used to solve the continuous query. Moreover, the trajectory segment is used for querying past location estimation of moving objects. The method of indexing moving objects data is also discussed to improve the querying process. Moreover, in reality, ERS operates in distributed heterogeneous environment. In addition to the issue associated with the development of MODGERS, the issue related to interoperability has also been highlighted. The approach of interoperability using ontology and available standard such as XML/GML is discussed in this research. Additionally, the example of interoperability scenario in MODGERS is presented to provide the real view of the problem. In the end, the generic model and interoperability framework can be extended to be applied to other problems.